(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the effect of intramammary application of curcumin in ewes with subclinical mastitis and healthy ewes on milk production, milk quality and ewes health. For this, two experiments were carried out: Experiment I: 10 ewes with chronic subclinical mastitis were divided into two groups of five ewes each: a) control, 3 mL of mineral oil was applied intra-mammary; b) curcumin, applied 2 mg of curcumin diluted in mineral oil, intra-mammary. There was a treatment effect, that is, ewes that received the application of curcumin had higher milk production. There was a treatment effect for the percentage of protein in milk, as well as a trend of treatment effect for lactose and total solders; with emphasis on lower levels of protein, lactose and non-fat solids in the ewes of the curcumin group compared to the control. We found an interaction between treatment versus day for milk protein on days 7 and 14 after application; lower in the curcumin group. Day effect was verified for erythrocyte and leukocyte counts, as well as hemoglobin concentrations in both groups. For experiment II we used 80 ewes divided into 4 groups: control, T2, T3 and T4 (2, 3 and 4 mg of curcumin diluted in mineral oil via intra-mammary, respectively). Day effect was observed for the T2 group, that is, there was an increase in milk production from day 1 to 20. Somatic cell count (SCC) was effected by treatment, day and interaction between treatment versus day. The highest SCC was observed in the T4 group. Of the group of ewes, 17 had problems in the mammary gland after applying the four treatments, and five ewes developed severe environmental mastitis and died; and the other animals also tested positive for subclinical mastitis in the racket test (California Mastitis Test). In general, the use of curcumin intra-mammary at the doses tested has no curative effect, as well as when used in healthy sheep, it has a negative effect, affecting the quality of the milk (increased CCS). Furthermore, the application of intra-mammary products (mineral oil or oil + curcumin) is a high risk for the animal; therefore, we do not recommend.